Neuroblastoma chemotherapy can be augmented by immunotargeting O-acetyl-GD2 tumor-associated ganglioside. (2nd January 2018) - Faraj, S.; Bahri, M.; Fougeray, S.; El Roz, A.; Fleurence, J.; Véziers, J.; Leclair, M. D.; Thébaud, E.; Paris, F.; Birklé, S.
ABSTRACT: Despite recent advances in high-risk neuroblastoma therapy, the prognosis for patients remains poor. In addition, many patients suffer from complications related to available therapies that are highly detrimental to their quality of life. New treatment modalities are, thus, urgently needed to further improve the efficacy and reduce the toxicity of existing therapies. Since antibodies specific for O-acetyl GD2 ganglioside display pro-apoptotic activity against neuroblastoma cells, we hypothesized that combination of immunotherapy could enhance tumor efficacy of neuroblastoma chemotherapy. We demonstrate here that combination of anti-O-acetyl GD2 monoclonal antibody 8B6 with topotecan synergistically inhibited neuroblastoma cell proliferation, as shown by the combination index values. Mechanistically, we evidence that mAb 8B6 induced plasma cell membrane lesions, consistent with oncosis. Neuroblastoma tumour cells treated with mAb 8B6 indeed showed an increased uptake of topotecan by the tumor cells and a more profound tumor cell death evidenced by increased caspase-3 activation. We also found that the combination with topotecan plus monoclonal antibody 8B6 showed a more potent anti-tumor efficacy in vivo than either agent alone. Importantly, we used low-doses of topotecan with no noticeable side effect. Our data suggest that chemo-immunotherapy combinations may improve the clinical efficacy and safety profile of current chemotherapeutic modalities of neuroblastoma.